COMPETENCE IMPLEMENTATION TEACHER PEDAGOGY IN IMPROVING QUALITY OF LEARNING IN SCHOOLS - Nurfuadi Nurfuadi (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
The purpose of this study was to analyze the pedagogic PAI subject teacher competence to improve the quality of learning in a comprehensive manner both in terms of the affective, cognitive and psychomotor domains. Research methods with specific processes to solve problems that will be studied about the quality of learning. Research to be defined as a tool to parse and explain how the quality of learning can be improved. Data collection techniques were obtained through a variety of methods, namely interviews with teachers, students, education staff and vice principals, observations at school locations observing phenomena that occur as a complement to data, documentation studies from office meeting notes, archives, curriculum and discussions of pedagogic research focus Teacher. Conclusion Islamic Religious Education Teachers at Aliyah Schools/Madrasahs have an important role in managing learning so that they can improve the quality of good and professional learning. A competent, intelligent teacher will be able to carry out the mandate in teaching students in a professional and responsible manner. The main competence that should be attached to the figure of a teacher is pedagogic competence so that he is able to manage learning professionally. Teacher pedagogical abilities can be expected independently, in increasing their professionalism in improving the quality of student learning.